Nazwy tkanin wschodniego pochodzenia w osiemnastowiecznej polszczyźnie (na przykładzie materiału z dwóch inwentarzy skarbca archikatedralnego kościoła ormiańskiego we Lwowie) = The names of textiles of Eastern provenance in the eighteenth-century Polish language (a study based on two inventories of treasury of the Armenian cathedral in Lvov) - Żuraszek-Ryś, Iwona (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The subject of this article are the names of textiles of Eastern provenance in the eighteenth-century Polish language. The research material was obtained from two inventories of treasury of the Armenian cathedral in Lvov, written in the Polish language and currently held in the Ossolineum Library in Wroclaw.
Keywords: polszczyzna; orientalizm; tkanina; nazwa; 18 w.; Polish language; orientalism; name; textiles